A Low-Temperature Hydrothermal Synthesis of Prussian Blue Nanocrystal and Its Application in H2O2 Detection - J. Yang; D. H. Li; L. L. Ji (Journal of Chemistry)
Uniform Prussian blue Fe3[Fe(CN)6]2 nanocrystals were synthesized by a direct dissociation and reduction of the single-Fe(III)-source precursor K3Fe(CN)6 under low-temperature hydrothermal conditions. UV-visible absorption spectrum, Fourier transform infrared spectrum, X-ray diffraction, field emission scanning electron microscope, X-ray photoelectron spectra, high-resolution transmission electron microscopy, and electrochemical testing were used to characterize and verify the synthesized Prussian blue nanocrystal product. The size of the synthesized product had a strong dependence on the acidity condition and the concentration of K3Fe(CN)6 solution. This result may facilitate not only the exploration of preparing Fe3[Fe(CN)6]2 nanocrystals for particular applications but also an in-depth explanation of the nature of the hydrothermal reaction. The Prussian blue nanocrystals were deposited onto an electrode support through lyotropic liquid crystalline templates to detect hydrogen peroxide (H2O2) by reduction reaction. Cyclic voltammograms showed that the Prussian blue modified electrode was of excellent electrocatalytic activity for H2O2. This electrode demonstrated a detection limit (1 × 10−7 M) and a linear range starting from the detection limit and extending over 6 orders of magnitude of H2O2 concentrations (1 × 10−7 to 1 × 10−1 M), which was of excellent performance in detecting H2O2.